Dragon age, volume 3 ebook Until we sleep. - Gaider, David (Dragon Age, 2013)
The lead writer of BioWare's hit Dragon Age games concludes King Alistair's epic quest—in a journey beyond reality itself! Fans around the world have recognized the Dragon Age comics to be an integral addition to the video-game saga. Now, series writer David Gaider pits King Alistair and his noble companions Varric and Isabela against their most nefarious foe—the twisted blood mage Aurelian Titus! An essential read while you wait for Dragon Age III! from Dragon Age lead writer DAVID GAIDER!